Larvicidal activity and chemical composition of essential oils against Aedes aegypti Linn (Diptera: Culicidae) and Aedes albopictus Skuse (Diptera: Culicidae) - Martins, Victor Emanuel Pessoa; Sampaio, Caroline de Góes; Faustino, Francisca Trifêna Silva; Silva, Abel Brasil Ramos da; Ribeiro, Paulo Riceli Vasconcelos; Rodrigues, Alzeir Machado; Canuto, Kirley Marques (Journal of Health & Biological Sciences, 2024)
Introduction Aedes mosquitoes are the main vectors of the dengue, chikungunya, and Zika viruses. Essential oils have been used in research as alternatives to the synthetic insecticides traditionally used in programs to control these diseases. Methods: leaves of plants from the Caatinga biome were used to obtain essential oils which were used for larvicide essays against Aedes aegypti and Aedes albopictus larvae. Results: significant differences were observed in the LC50 values of C. zeylanicum, C. winterianus, E. citriodora, O. micranthum, and T. erecta essential oils in Ae. aegypti, while these differences were observed for A. conyzoides, C. winterianus, E. citriodora, and O. micranthum essential oils in Ae. albopictus, at the analyzed times. The LC50 for 24 h revealed a significant larvicidal effect for all tested samples, with emphasis on the effect of A. conyzoides and L. gracilis essential oils on Ae. aegypti, and the effect of A. conyzoides, C. zeylanicum, C. winterianus, L. gracilis, and O. micranthum essential oils on Ae. albopictus, all with an LC50 < 100 ppm. It was observed a predominance of terpenes as components in the essential oils, and, in some of them, representing the major constituent (citronellal: 47.71% in E. citriodora and 47.63% in C. winterianus; geraniol: 30.54% in C. winterianus; citronellol: 25.61% in E. citriodora; carvacrol: 55.13% in L. gracilis; and cyclohexen-1-one, 2-isopropyl-5-methyl-: 69.94% in T. erecta). The other major compounds observed were precocene (chromene - 97.66% - A. conyzoides), and eugenol (phenylpropanoid - 96.28% and 73.21% - C. zeylanicum and O. micranthum, respectively). Conclusions: the findings of this study revealed the larvicidal potential of these essential oils on Ae. aegypti and Ae. albopictus control, representing an alternative source to the traditional chemical controls used against the populations of these vectors. Further studies on the effects on non-target organisms and the combined action of two or more essential oils evaluated under field conditions are essential for obtaining commercially efficient formulations of these extracts.